2013
DOI: 10.1016/s2221-1691(13)60168-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of larvicidal activity of Pongamia pinnata extracts against three mosquito vectors

Abstract: Pongamia pinnata L, Larvicidal, Mosquito vectors, Culex quinquefasciatus, Aedes aegypti, Anopheles stephensi Objective: To evaluate the mosquito larvicidal activity of Pongamia pinnata (P. pinnata) extracts against three mosquito vectors. Methods: The methanol and hydroalcohol extracts of bark part of P. pinnata L were tested against fourth instar larvae of Culex quinquefasciatus, Aedes aegypti and Anopheles stephensi. The mortality was observed 24 h and 48 h after treatment, data was subjected to probit analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Guna et al [1] reported the larvicidal activity of Pongamia pinnata methanol and hydroalcoholic extracts against three mosquito vectors Culex quinquefasciatus , Aedes aegypti and Anopheles stephensi . In their studies, the hydroalcoholic extract of Pongamia pinnata showed a significant mortality in three mosquito larvae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guna et al [1] reported the larvicidal activity of Pongamia pinnata methanol and hydroalcoholic extracts against three mosquito vectors Culex quinquefasciatus , Aedes aegypti and Anopheles stephensi . In their studies, the hydroalcoholic extract of Pongamia pinnata showed a significant mortality in three mosquito larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The word malaria means ‘bad air’ which was originated from the Italian words ‘mal’ and ‘aria’ [1]. Malaria is an extremely dangerous parasitic disease infected by the protozoan parasites Plasmodium falciparum , Plasmodium vivax , Plasmodium malariae and Plasmodium ovale.…”
Section: Introductionmentioning
confidence: 99%